A 30-year experience in using oral methotrexate as initial treatment for gestational trophoblastic neoplasia regardless of risk group. (1st February 2016) - Faaborg, Louise; Niemann, Isa; Ostenfeld, Eva B.; Hansen, Estrid S.; Sunde, Lone; Lindegaard, Jacob C.
Abstract : Background. Treatment of postmolar gestational trophoblastic neoplasia (GTN) is often stratified according to FIGO score using methotrexate (MTX) for low-risk patients and first-line multi-agent chemotherapy (e.g. EMA-CO) for high-risk patients. In contrast, oral MTX may be given as first-line therapy to all GTN patients regardless of risk group. The aim was to examine the efficacy of oral MTX and a response-adapted treatment policy, which has been used for three decades at Aarhus University Hospital (AUH). Material and methods. Seventy-one consecutive postmolar GTN patients treated 1981–2011 were included. Data were obtained from medical records, using histopathology and human choriogonadotropin (hCG) to verify the diagnosis. All patients received oral MTX as first-line chemotherapy. Second- and third-line chemotherapy was given according to response. Results. Sixty-four (90%) patients were retrospectively categorized as FIGO low-risk disease, whereas seven patients (10%) had high-risk disease. Complete response to first-line oral MTX chemotherapy was observed in 35/71 (49%) patients, while 62/71 (87%) had complete remission on MTX (first-line) and/or MTX plus dactinomycin (second-line), without the use of multi-agent therapy. Nine patients (13%) received third-line multi-agent chemotherapy, six low-risk (67%) and three high-risk (33%) patients. There were no recurrences and no patients died as a consequence of toxicity or disease. Conclusion. Fifty percent of all patients can be cured on oral MTX alone. By adding dactinomycin, about 90% are cured without use of multi-agent chemotherapy. The use of oral MTX as initial treatment can minimize the number of patients receiving multi-agent chemotherapy.